Air Pollution, Physical Activity, and Cardiovascular Function of Patients With Implanted Cardioverter Defibrillators: A Randomized Controlled Trial of Indoor Versus Outdoor Activity. Issue 4 (April 2020) - Liu, Ling; Urch, Bruce; Nanthakumar, Kumaraswamy; Chen, Li; Smith-Doiron, Marc; Brook, Jeffrey R.; Speck, Mary; Silverman, Frances; Stieb, David M.
Abstract : Objective: To investigate whether implanted cardioverter defibrillator (ICD) patients exercising indoors on higher air pollution (AP) days had reduced adverse cardiovascular effects compared with those exercising outdoors. Methods: Eighteen participants were randomly divided into control or intervention groups. Blood pressure (BP), pulse rate (PR), and oxygen saturation (O2 SAT) were measured daily before and after participants walked outdoors for 30 minutes. On days with higher forecast AP the intervention group exercised indoors. Results: AP was significantly associated with increased BP and PR, and reduced O2 SAT. After adjustment for exercise levels, AP was associated with increased diastolic BP and PR in controls only. Significant improvements in cardiovascular measures over time were observed in both groups. Conclusion: In ICD patients, reducing AP exposure may reduce adverse cardiovascular effects, while daily mild exercise may benefit cardiovascular function. Abstract : Supplemental Digital Content is available in the text